Fluxo e refluxo Rio-Belém: a presença de poetas-tradutores modernistas nos suplementos literários letras e artes (1946-1954) e arte-literatura (1946-1951) - LOPES, Eldinar Nascimento (Universidade Federal do Pará, 2019)
The Present study aims to catalog the literary translations published in literary supplements Arte-Literatura, between 1946-1949, and Letras & Artes, in the period from 1946 to 1954, in the states of Pará and Rio de Janeiro, respectively, to propose a comparative study between them and understand what foreign literatures were widespread at that time and what are the differences and similarities between the translated materials. Moreover, it is necessary to understand the extent to which the translations flow and the presence of foreign authors became indispensable for the expansion project of educational reading, both regarding to interests facing the ideological purposes but also aesthetic. Using as a parameter the post-war period and the unblocking of the New State policy, the circulation of literary productions from different places and different times was very important to recognize the various forms of literary creations and an opening to the multiplicity of cultures mainly to consider the importance of dialogue and inclusion among diverse cultures. In this context of intercultural and intellectual openness to other ways of thinking, the translator's presence plays an important role as a transformer agent, especially when you discover the effort that our writers and translators had to disclose a literature increasingly broad, heterogeneous and critical. At the same time, the cataloging work showed that there was a huge variety of writers and translators, known or not.